Pengaruh Persepsi Harga, Promosi, Dan Keamanan Terhadap Keputusan Penggunaan Canva Pada Mahasiswa Di Jakarta - Anisa Nur Afnisari; Sonny Indrajaya (Universitas Mercu Buana, 2021)
The purpose of this study is to discuss the factors that influence the decision to purchase Paid Features on the Canva Application. The independent variables obtained from the results of the preliminary survey are Perceptions of Price, Promotion, and Security. While the dependent variable to be obtained is the Purchase Decision. Methods of data analysis using Variance Based Structural Equation Modeling Partial Least Square (PLS) and Statistical Product andService Solutions (SPSS). The sample that will be used in this study are students who live in the DKI Jakarta area as many as 200 respondents. The sampling technique used is the Stuctural Equation Model (SEM). By using a quantitative descriptive approach. The results of this study indicate that Price Perception has a significant positive effect on purchasing decisions, Promotion has a significant positive effect on purchasing decisions and Security has a significant positive effect on purchasing decisions.